Polygonum minus essential oil modulates cisplatin-induced hepatotoxicity through inflammatory and apoptotic pathways - Abd Rashid, Norhashima; Hussan, Farida; Hamid, Asmah; Adib Ridzuan, Nurul Raudzah; Halim, Syarifah Aisyah Syed Abdul; Abdul Jalil, Nahdia Afiifah; Najib, Nor Haliza Mohamad; Teoh, Seong Lin; Budin, Siti Balkis (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Oxidative stress, inflammation and apoptosis are thought as primary mediators of cisplatin-induced hepatotoxicity. The objective of this study was to determine the protective effect of Polygonum minus essential oil in cisplatin-induced hepatotoxicity. A total of forty-two male rats were randomly divided into seven groups: control, cisplatin, β-caryophyllene 150 mg/kg (BCP), PmEO 100 mg/kg + cisplatin (PmEO100CP), PmEO 200 mg/kg + cisplatin (PmEO200CP), PmEO 400 mg/kg + cisplatin (PmEO400CP) and PmEO 400 mg/kg (PmEO400). Rats in the BCP, PmEO100CP, PmEO200CP, PmEO400CP and PmEO400 group received respective treatment orally for 14 consecutive days prior to cisplatin injection. All animals except for those in the control group and PmEO400 were administered with a single dose of cisplatin (10 mg/kg) intraperitoneally on day 15 and all animals were sacrificed on day 18. PmEO100CP pretreatment protected against cisplatin-induced hepatotoxicity by decreasing CYP2E1 and indicators of oxidative stress including malondialdehyde, 8-OHdG and protein carbonyl which was accompanied by increased antioxidant status (glutathione, glutathione peroxidase, superoxide dismutase and catalase) as compared to cisplatin group. PmEO100CP pretreatment also modulated changes in liver inflammatory markers (TNF-α, IL-1α, IL-1β, IL-6 and IL-10). PmEO100CP administration also notably reduced cisplatin-induced apoptosis significantly as compared to cisplatin group. In conclusion, our results suggested that P. minus essential oil at a dose of 100 mg/kg may protect against cisplatin-induced hepatotoxicity possibly via inhibition of oxidative stress, inflammation and apoptosis.
EXCLI Journal;Vol. 19. 2020, pp.1246-1265
Keywords: Apoptosis; Cisplatin; Hepatotoxicity; Inflammation; Polygonum minus essential oil; Oxidative stress; 610